Clustered Cobalt Nanodots Initiate Ferroptosis by Upregulating Heme Oxygenase 1 for Radiotherapy Sensitization (Small 10/2023). Issue 10 (10th March 2023) - Zhao, Jianqi; Chen, Yin; Xiong, Tainong; Han, Songling; Li, Chenwenya; He, Yingjuan; He, Yongwu; Zhao, Gaomei; Wang, Tao; Wang, Liting; Cheng, Tianmin; Wang, Cheng; et al.
Abstract : Radiotherapy Sensitization Enhancing the cellular radiosensitivity is instrumental for improving the efficacy of tumor radiotherapy. In article number 2206415, Junping Wang, Cheng Wang, and co‐workers report a tumor‐penetrating nanomaterial iCoDMSN constituted with dendritic mesoporous silica nanoparticles and iRGD peptide‐conjugated CoO@BSA nanodots. By decreasing KEAP1 expression and upregulating nuclear factor erythroid 2‐related factor 2 (NRF2) and heme oxygenase 1 (HMOX1), iCoDMSN expands the labile iron pool in cancer cells and initiates ferroptosis, whereby the nanomaterial sensitizes cancer cells to ionized radiation and eliminates the tumors combined with radiotherapy.